Analytical Study of The Impact of Administrative Leadership on Development Projects (The International Journal for Scientific Research, 2024)
The study addressed the role of leadership in achieving success and effective performance of projects in various sectors, as successful project management is a complex process that requires coordination between a specific group of elements and individuals, as the leader plays a major role in achieving success and achieving the desired goals. A successful leader must have certain qualities that enable him to manage the project accurately and develop a clear strategy to achieve the goals. The leader must be able to deal with the variables and risks that the project may face and must have the ability to make the right decision, so he must have strong skills in managing resources and organizing priorities. The importance of the study stems from clarifying effective leadership and its role in defining and clarifying the strategic objectives of development projects. The study is concerned with the possibility of forming a team and motivating individuals to make them work as a team, taking into account how to manage available resources and that they are limited, whether material or human resources. The study is also concerned with the skills of leaders in solving problems, facing challenges, making sound decisions, overcoming obstacles, and building strong relationships with beneficiary partners, stakeholders, and communities, and focusing on the professional and personal development of team members. The study is also concerned with clarifying the extent of the leader's ability to manage changes that may occur in the project and how to face challenges. This study seeks to achieve specific goals, including analyzing different administrative leadership methods and their impact on development projects, evaluating the role of leadership in improving the performance and success of development projects, and providing recommendations to improve leadership practices in the development sector. The study followed the qualitative, quantitative, analytical, comparative and case study approaches. The study's conclusion revolves around the impact of administrative leadership on development projects by addressing the concept of administrative leadership, the characteristics of a successful leader, and his role in the success and development of projects to achieve goals and success
Keywords: Administrative Leadership; Development Projects; Effective Performance